2022
DOI: 10.1177/23312165221078707
|View full text |Cite
|
Sign up to set email alerts
|

Self-motion with Hearing Impairment and (Directional) Hearing Aids

Abstract: When listening to a sound source in everyday situations, typical movement behavior is highly individual and may not result in the listener directly facing the sound source. Behavioral differences can affect the performance of directional algorithms in hearing aids, as was shown in previous work by using head movement trajectories of normal-hearing (NH) listeners in acoustic simulations for noise-suppression performance predictions. However, the movement behavior of hearing-impaired (HI) listeners with or witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…This explains the observed increase in both head and eye movement. The increase in eye movement aligns with some of the findings by Hendrikse et al 39 , who observed increased variability in gaze position for older and hearingimpaired participants listening to conversations in virtual environments. The longer head fixations in high-reverberant conditions may indicate an extended listening period before participants moved their heads to a new position.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This explains the observed increase in both head and eye movement. The increase in eye movement aligns with some of the findings by Hendrikse et al 39 , who observed increased variability in gaze position for older and hearingimpaired participants listening to conversations in virtual environments. The longer head fixations in high-reverberant conditions may indicate an extended listening period before participants moved their heads to a new position.…”
Section: Discussionsupporting
confidence: 89%
“…While there is an advantage of less direct head location to improve SNR, the task used in this study triggered visual search behavior, even though there was no benefit from the visual information. This might have led participants to make less use of the SNR benefit for head locations, similar to findings in studies investigating head orientations during conversations 33,39 . The SNR benefit of less direct head positions, however, may explain the higher final head orientation offset at the decision phase's end for high-reverberant scenes 33,39 .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Several patient-dependent factors have an impact on sound source localization skills, but studies on adults and children show large amounts of variability across listeners even with similar backgrounds. There can even be changes in everyday listening behavior associated with hearing loss and hearing aid use [ 44 ]. Further research is needed to clarify all these aspects.…”
Section: Discussionmentioning
confidence: 99%
“…A quantitative analysis of active listening hence may pave the way for the use of new methodologies in auditory localization studies, capable of objectively characterizing the listeners' spatial listening strategies 46 also based on their motor behavior in a controlled acoustic ecology. Furthermore, based on the positioning of the head-mounted devices and their orientation angle when the target was hit, the data acquired during a test session might be used to train dynamic and adaptive algorithms enhancing the directionality of cochlear implants and hearing aids.…”
Section: Discussionmentioning
confidence: 99%